TINJAUAN HTUKUM INTERNASIONAL TERHADAP TERJADINYA PELANGGARAN HAM DI INDONESIA - Kadek Yopi Sri Wahyuni (Jurnal Locus Delicti, 2022)
Human Rights are a set of rights inherent in the nature and existence of humans as creatures of God Almighty and His grace, respected, legalized, and protected by the state, law, government, and all for the honor and protection. Therefore, human rights are inherent human rights and must be respected, protected and protected by all individuals or society as a natural and fundamental gift. In essence, efforts to respect, protect, and enforce human rights are a shared obligation and responsibility of individuals, the government, and the nation. However, Indonesia is not yet independent and there are many human rights violations, so there are still many cases of human rights violations in Indonesia. Human rights violations are caused by internal and external factors. Internal factors such as egoism, low awareness of human rights, and intolerance. External factors such as abuse of power, indecision by law enforcement officers, abuse of technology, and high levels of social and economic inequality.